Antibacterial, antioxidant, cytotoxic effects and GC-MS analysis of mangrove-derived Streptomyces achromogenes TCH4 extract - Tangjitjaroenkun, Janpen; Pluempanupat, Wanchai; Tangchitcharoenkhul, Rungnapa; Yahayo, Waraporn; Supabphol, Roongtawan (Archives of Biological Sciences, 2021)
Paper description: Mangrove-derived Streptomyces can produce a wide range of bioactive secondary metabolites. The extract of mangrove-derived Streptomyces achromogenes strain TCH4 was evaluated by determining antimicrobial, antioxidant and cytotoxic properties. Chemical constituents were analyzed by gas chromatography-mass spectrometry. The main compounds of the extract were pyrrolo[1,2-a]pyrazine-1,4-dione, hexahydro-3-(2-methylpropyl) (36.85%), benzeneacetamide (23.76%) and deferoxamine (12.85%). The extract of achromogenes TCH4 produced antibacterial, antioxidant and cytotoxic effects. achromogenes TCH4 is a potential natural agent for biomedical and pharmaceutical applications. Abstract: The in vitro biological activities of the ethyl acetate extract of the culture filtrate from Streptomyces achromogenes TCH4 (TCH4 extract) were evaluated. The ethyl acetate extract of TCH4 produced a bacteriostatic effect against Enterobacter cloacae, Staphylococcus aureus, Staphylococcus saprophyticus, Bacillus subtilis, methicillin-resistant S. aureus (MRSA) and Klebsiella pneumoniae. The extract had bactericidal activity against S. aureus, S. saprophyticus, S. aureus (MRSA) and K. pneumoniae with minimum bactericidal concentration (MBC) values in the range of 500-1000 µg/mL. The total phenolic and flavonoid contents in TCH4 extract were 107.20±2.57 mg gallic acid equivalent (GAE)/g and 44.91±0.84 mg quercetin equivalent (QE)/g of dry extract. Antioxidant activity was determined by DPPH radical (IC50 299.64±6.83 µg/mL) and ABTS radical scavenging (IC50 65.53±0.95 mg/mL), and the ferric-reducing antioxidant power (FRAP) (822.76±9.12 mM FeSO4.7H2O/g dry extract) assays. TCH4 extract exhibited cytotoxic activity in the DU-145 cell line (IC50 9.36±0.37 mg/mL). Analysis of extract constituents by GC-MS revealed pyrrolo[1,2-a]pyrazine-1,4-dione, hexahydro-3-(2-methylpropyl) (36.85%), benzeneacetamide (23.76%), and deferoxamine (12.85%) as the major compounds, which have been reported to possess pharmaceutical properties. S. achromogenes TCH4 could be a potential source of bioactive metabolites with antibacterial, antioxidant and anticancer activities for pharmaceutical applications.